Analysing process-induced deformation and stresses using a simulated manufacturing process for composite multispar flaps. (February 2015) - Brauner, Christian; Bauer, Stefan; Herrmann, Axel S
Although composite materials have numerous advantages, some disadvantages, including high manufacturing costs, are relevant. In particular, if the material is applied to large structural components, such as the wings, flaps or fuselage of an airplane, efficient manufacturing processes are required to generate products that are both high quality and cost effective. Therefore, monolithic designs often become integral due to the lower overall part count and simplified designs (e.g. reducing the number of joints and fasteners significantly). For highly integrated monolithic structures, developing a robust manufacturing process to produce high quality structures is a major challenge. An integral structure must conform to the tolerance requirements because those requirements may change. Process-induced deformations may be an important risk factor for these types of structures in the context of the required tolerances, manufacturing costs and process time. Manufacturing process simulations are essential when predicting distortion and residual stresses. This study presents a simulation method for analysing process-induced deformations on the structure of a composite multispar flap. The warpage depends on the thermal expansion and shrinkage of the resin. In this study, a sequentially coupled thermo-mechanical analysis of the process will be used to analyse temperature distribution, curing evolution, distortion and residual stresses of 7.5 m long composite part.